A. PIERIS (ed.) - Architecture on the Borderline: Boundary Politics and Built Space - Tobías González, Javier (ZARCH, 2020)
Anoma Pieris (ed.)Architecture on the Borderline: Boundary Politics and Built SpaceOxon: Routledge, 2019, 288 págs. Encuadernación en rústica. Idioma: inglés. 42,33€.ISBN: 978-11-381028-2-8